Development of runoff simulation model using excel - Loo, Wai Leong. (2010)
In this study, based on kinematic wave theory, a runoff simulation model has been developed for the flow on an overland plane and in channels of nine different shapes. The channel shapes are square, wide rectangular, deep rectangular, triangular, vertical curb, parabolic, circular, trapezoidal with equal side slope and trapezoidal with one side vertical. In addition to that, a reservoir routing model has also been developed. For verification, the runoff simulation model has been applied to two artificial and one natural catchment. The two artificial catchments consist of a concrete plane and a concrete catchment. The natural catchment is the Upper Bukit Timah catchment. The reservoir routing model is applied to three case studies. The runoff simulation model has been applied to a rainfall event for the two artificial catchments and for the Upper Bukit Timah catchment. For the artificial catchments, the comparison of simulated and observed hydrographs shows that they are nearly perfect fit, and for the Upper Bukit Timah catchment, the comparison shows that they are very good fit. For the reservoir routing model, the simulated hydrograph and the hydrograph routed by traditional methods from the three case studies are very good fit. The runoff simulation model is therefore a reliable tool for simulating runoff over a plane, in a channel and through a reservoir.